The impact of isolation on the health of adolescents with low socioeconomic status: A longitudinal study during the Covid-19 pandemic - Derzsi-Horváth, Martina; Bánfai-Csonka, Henrietta; Masa, Andrea; Bánfai, Bálint; Kívés, Zsuzsanna; Szabó, Attila; Deutsch, Krisztina (Kontakt, 2024)
Introduction: The main objective of our research was to measure the impact on health of isolation and online education due to the Covid-19 pandemic, and particularly risk behaviours and mental health in adolescents with low socioeconomic status. Methods: We used an online questionnaire before (Q1) and after (Q2) the introduction of digital education, which was completed by a total of 212 Hungarian secondary school students. We measured the prevalence of risk behaviours and psychosomatic symptoms: subjective well-being, life satisfaction, self-esteem, sense of coherence, and changes in coping mechanisms among the students. Results: Stable smoking (p = 0.316), alcohol consumption habits (p = 0.573), and cannabis use (p = 0.607) did not change significantly between the two data sets. Psychosomatic symptoms (p = 0.111), life satisfaction (p = 0.727), self-esteem (p = 0.053) and sense of coherence (p = 0.602) also showed no significant change. However, there was an increase in the level of subjective well-being (p = 0.017) and in the proportion of those who used cognitive restructuring (p = 0.035) or problem-focused coping (p = 0.012) as coping mechanisms. Conclusion: Digital education had no negative impact on the health indicators of the students with low socioeconomic status. There were no significant changes in risk behaviours between the two surveys, while the students' mental health changed in a positive direction in several aspects.
Keywords: Surveys and Questionnaires; Psychology, Adolescent; Mental Health; Humans; Correlation of Data; nízký socioekonomický status; Education, Distance; Low Socioeconomic Status; psychosomatické poruchy; duševní zdraví; korelace dat; Psychophysiologic Disorders; lidé; psychologie adolescentů; průzkumy a dotazníky; COVID-19; sociální izolace; Health Risk Behaviors; Adolescent; Statistics as Topic; Social Isolation; statistika jako téma; zdravotně rizikové chování; mladiství; distanční studium